ELSA 2014 Cohort: Risk Factors Associated With Heavy Episodic Drinking Trajectories in Argentinean College Students - Vera, Belén del Valle; Pilatti, Angelina; Pautassi, Ricardo Marcos (Frontiers in Behavioral Neuroscience, 2020)
Heavy episodic drinking (HED) is highly prevalent in college students. In Argentina, there is a notable lack of longitudinal studies examining drinking trajectories. The present study identified HED trajectories in Argentinean college students during the first three years of college (seven waves) and examined the association between risk factors for alcohol use and HED trajectories. The sample was composed by 1240 college students [63.1% women, aged 18-25 years (M=19.1±1.7)] who completed at least three waves (the first data collection and ≥2 follow-ups). For three years, participants completed seven surveys that measured HED frequency, age of drinking onset, drunkenness occurrence, trait impulsivity, family history of alcohol abuse, stressful life events and perceived peer´s drinking. Latent Class Growth Analysis and Multinomial Logistic Regression were used to identify the pattern and number of HED trajectories, respectively, and to explore which risk factors better distinguished between the trajectories. Six HED trajectories were identified: Heavy Stable Frequency, Moderate Stable Frequency, Moderate Decreasing Frequency, Stable Infrequent, Decreasing Infrequent and No-HED. A younger age of drinking onset, alcohol intoxication, greater perception of peer drinking frequency and higher levels of impulsivity (i.e., sensation seeking, lack of premeditation and positive urgency) increased the probability of belonging to the trajectories with more frequent HED. These trajectories partially coincide with those identified in studies from other cultures. Unlike previous studies, we did not find a trajectory with increasing/ascending HED frequency. This may be related to contextual/cultural variables unique of Argentina, like differences in the age when the peak in alcohol consumption is reached or the legal minimum age to buy alcoholic beverages in this country, and the idiosyncratic elements that characterize college life in Argentina. This work represents a step forward in the identification of risk factors differentiating between different HED trajectories, and help understand changes in alcohol use during college, in an understudied population.